Modified Newtonian Gravitational Theory: Resolving Galactic Anomalies - SalShurman, Ali (Journal of Research in Vocational Education, 2025)
For more than a hundred years Quantum Mechanics and the Standard Model have dominated physics using the motto "At the level of the very, very small, things obey different rules". The ethos behind this motto was implemented using wave-particle duality. Now "Augmented Newtonian Dynamics" has shown in a definitive manner that Newtonian dynamics prevail even at the level of the very, very small. The nature of gravity has intrigued scientists for centuries. While its mechanisms were described in detail by Newton and later refined by Einstein, the underlying reason for its existence remains an open question. Newton's law of universal gravitation provided a mathematical framework that accurately predicted the motion of celestial bodies and the behaviour of objects on Earth. However, Newton acknowledged the lack of an explanation for the underlying cause of gravity. He proposed the existence of a medium, or "aether," through which gravitational forces might propagate, but was unable to provide experimental evidence for its presence. The worked examples in this paper prove that Newton's conjecture of an aether that permeates the Universe is proven beyond doubt.